Characterisation of an electromechanical clutch for continuously variable transmission (CVT) application - Tawi, Kamarul Baharin (Faculty of Mechanical Engineering, 2008)
A manual friction clutch has been modified by applying a dc-motor actuator, such that the clutch can be operated electronically. In order for this electro-mechanical clutch suits for CVT applications, the fundamental research to study the characterisation of the clutch needs to be carried out. This study focused on the clutch dynamic behaviours, especially during the engagement and disengagement processes when the clutch was operated manually in open loop system without any control strategy applied to it. The observed parameters were torques, speeds and powers of both engine and output clutch. The experimental results show that during engagement process, small overshoot occurred at output clutch speed, but significant overshoots occurred at input and output torque as well as power. The output torque overshoot was not only directly proportional to the initial engine speed but also inversely proportional to the output load torque.